Motivation at Work of Resident Tutors at Nottingham University Halls of Residence - Thoai, Le (2018)
Purpose: The research investigates the factors that influence the motivation to volunteer and engage in the job of resident tutors within the setting of Nottingham University Halls of Residence. Design/methodology/approach: Qualitative interviews were conducted with a sample of ten individuals who have been working as resident tutors across University halls. An ethnographic approach was also applied as a complement to the main method of interviewing. Findings: Results show that resident tutors’ motivation is shaped by a variety of factors such as benefits provided, the nature of the job, the intention to gain experience and skills for future careers, helping others as an altruistic reason, and interpersonal relationships at work. Implications: Overall, tutors are both motivated by internal and external motivators although they are more likely to be encouraged by the external ones. Tutors are significantly demotivated by the nature of their work and unequal treatment in terms of accommodation, rules and practices. Meanwhile, their motivation is not influenced by the expectation of rewarding outcome or by establishing personal objectives. Finally, it is argued that tutors vary their motivation at work on a social relationship continuum from positive engagement to no involvement to unfavourable conflicts. Originality/value: The study is expected to provide managerial implications for the University Halls of Residence Pastoral Support System (including Head of Student Welfare, Wardens, Deputy Wardens) in terms of managing and motivating resident tutors working in University Halls. It also contributes to the understandings of volunteers’ motivation and provides insights into volunteering within the context of the University of Nottingham.